"Click First!": The Effects of Instant Activism Via a Hoax on Social Media. (April 2020) - Park, Keonyoung; Rim, Hyejoon
To facilitate the immediate effects of social media activism, some activists adopt a deceptive strategy, swaying lay individuals' perceptions and manipulating their behavior despite ethical considerations. This study identified instant activism, which targets lay individuals' effortless supportive actions (e.g., clicking) on social media and examined its effects in the context of GMO (genetically modified organisms) labeling issues in the United States. Grounded in the situational theory of problem solving, this study investigated who engages in instant activism and what their behavioral consequences are. Results of an online survey ( n  = 483) suggested that (a) individuals with a low level of issue knowledge but a high level of issue involvement tend to believe a social media hoax and (b) belief in the hoax leads individuals to engage in active communicative activities that involve problem solving and behavioral changes when mediated by situational motivation. Theoretical and practical implications were discussed.